Indigenous Knowledge for Disaster Risk Mitigation: Field Notes from Nepal’s Four Districts - Luintel, Youba Raj (Academic Voices: A Multidisciplinary Journal, 2018)
Nepal is a small but vastly mountainous and highly disaster-prone country. The country is exposed to multi-hazards. The field observation reveals that there exists a rich repertoire of indigenous knowledge for disaster risk mitigation in Nepal, which is neither incorporated in the modern education system nor recorded in any systematic manner. Still, such knowledge and practice continue to exist. Studies reveal that communities have a rich stock of knowledge on the way they design housing and settlement pattern that would best mitigate the risk of disaster. Communities also practice afforestation; agro-forestry; mixed and inter-cropping; and drywall fencing or bio fencing. They also build terraces and terrace walls; construct ponds; and consolidate riverbanks to avoid the risks of disasters. They learn this all from conventional knowledge and hand over to the next generation by way of practice. Drawing information from four districts of Nepal, this paper draws a policy conclusion that well before they disappear, the existing repertoire of the diverse forms of indigenous knowledge needs to be documented, and blended with science-based knowledge. This can also be logically concluded that Nepal can demonstrate in this sector by taking a lead.